The EFL Students’ Perceptions on the Plagiarism in Writing Thesis Proposals: A Case Study - Lenny Marzulina; Rizqy Dwi Amrina; Dian Erlina; Muhamad Holandyah; Raudhatul Jannah; Herizal Herizal; Kasinyo Harto (Indonesian Research Journal in Education |IRJE|, 2022)
This study aimed to investigate the plagiarism phenomenon in thesis proposal writing by EFL students of UIN Raden Fatah Palembang through their perceptions. The data of this qualitative case study were obtained through interviews with the research participants. They were selected based on the results of the Turnitin plagiarism checker for their thesis proposals. Thematic analysis was carried out to analyze the research data. We found that the students had similar perceptions of plagiarism, both in general and academic writing contexts, but they had various perceptions of the forms of plagiarism. Some of them were unaware of committing plagiarism in their thesis proposals. They were familiar with the term paraphrasing to avoid plagiarism, but they could not paraphrase the quotations properly in writing their proposals. Unawareness about plagiarism, lack of knowledge and practice for proper paraphrasing, getting stuck while writing, laziness in writing, and easiness of getting information from the internet were the main contributing factors why they committed plagiarism in their works.